Geochemical characteristics of geothermal and hot spring gases in Beijing and Zhangjiakou Bohai fault zone - Yang, Mingbo; Liu, Guiping; Liu, Zhe; Ma, Jingchen; Li, Liwu; Wang, Zhiguo; Hua, Peixue; Xing, Lantian; Sun, Xiaoru; Han, Kongyan; Cui, Bowen; Wu, Xiaodong (Frontiers in Earth Science, 2022)
Zhangjiakou Bohai seismic belt(hereinafter referred to as ZHJK-BHF)belong to a group of orderly active NW-NWW fault zones, where high level seismic activities occurred and is rich in geothermal resources since Cenozoic. Many large earthquakes occurred here, which has become an important area for earthquake monitoring and research. In order to characterize the temporal and spatial variation of gas geochemistry in the ZHJK-BHF in the Capital circle, this paper used the related data of 23 geothermal hot springs in the West and east of the ZHJK-BHF, which obtained during the two previous investigations in 2013 and 2018. and to fill the gap of gas geochemistry for these hot springs in the middle of ZHJK-BHF in Beijing area, 21 hot spring gas samples were collected from October 2020 to November 2021. The test results of isotopic changes of helium, neon and carbon of these samples indicated that: (1) the range of helium isotope ratio (3He/4He (RC/Ra) )of hot spring gas varied 0.1~2.86Ra (Ra = air 3He/4He =1.39) × 10-6), the maximum proportion of mantle-sourced helium was 35.4%, which implied that although the geological fluid in the fault zone mainly came from the crust, the mantle-sourced helium was rather considerable. Hot spring gas in Beijing is mainly composed of nitrogen, accounting for more than 69%, and the concentration of carbon dioxide is low, ranging from 0-6.1%, δ13cco2 varies from -19 ‰ to -9.6‰ (vs. PDB), showing the mixed characteristics of organic sediments and mantle sources. (2) the transition from mountainous area to plain in the central and western part of ZHJK-BHF, helium isotopes have obvious peak values; It means that there are more upwelling mantle source materials and more upwelling deep fluids in the ZHJK-BHF. Compared with regional seismicity, the results show that in the area with relatively strong upwelling of deep fluid in ZHJK-BHF, deep fluid plays an important role in controlling regional seismicity.